The role of peripheral vision during decision-making in dynamic viewing sequences - DeCouto, B. S.; Fawver, B.; Thomas, J. L.; Williams, A. M.; Vater, C. (Journal of Sports Sciences, 2023)
Decision-making in team sports necessitates monitoring multiple performers located at different distances (i.e., viewing eccentricities) from a critical information source. The processing of peripheral information is generally impaired under anxiety and when responding to stimuli located at larger eccentricities. These hypotheses have not been sufficiently tested in dynamic performance environments. We examined how pressure and eccentricities affect decision-making and visual behaviour in 4v4 basketball defensive scenarios using a head mounted display. Experienced players monitored plays from the first-person perspective (centre position) and made defensive steps towards opponents threatening the basket from different eccentricities under low- and high-pressure. To tax working memory, participants simultaneously performed a backward counting task. Players responded slower and with lower accuracy to opponents at larger eccentricities. Players mostly fixated on the ball-carrier, but over 50% of fixations were located on peripheral players, indicating that information in the periphery must be frequently updated with foveal vision (i.e., pivot strategy). When pressured, participants increased mental effort and improved counting performance; however, gaze behaviour and decision-making were relatively unaffected. Findings suggest that basketball players respond more quickly to opponents positioned at lower compared to higher eccentricities at the cost of impaired responses to opponents in the periphery.